Membina Karakter Aktivis Mahasiswa Melalui Mata Kuliah Pendidikan Kewarganegaraan - Kolo, Adriana; Ikbal, Asep (Universitas Nusantara PGRI Kediri, 2022)
This research is motivated by the development of student activism, especially at the University of Timor, East Nusa Tenggara. One of the manifestations of the activities of student activists can be seen from the demonstrations of students carrying campus attributes and alma maters. Demonstrations that are actually the mouthpiece of democracy become less than perfect when they are colored by unethical actions when expressing their aspirations, such as using harsh words, violating demonstration rules and destroying public facilities. The people really expect the role of students but not with unethical actions, so it is the duty of the campus to foster the character of student activists to become plenary students. This study tries to explain the role of Citizenship Education courses in fostering the character of student activists at the University of Timor. Literacy studies and case studies were chosen as methods in this research so that they can find the formulation of the coaching model. This study uses a qualitative approach so that it can find facts in depth through interviews, observations and literacy studies as a comparison of character building for student activists as well as elaborating an appropriate model to cultivate the character of students who have Pancasila democracy